EDUKASI PENGGUNAAN OBAT BERBASIS KUNJUNGAN RUMAH UNTUK MENINGKATKAN PENGETAHUAN MASYARAKAT DI NAGARI SIKUCUR, KABUPATEN PADANG PARIAMAN - Lailaturrahmi Lailaturrahmi; Elsa Badriyya; Annisa Fauzana; Dita Permatasari (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
The trend of independent drug use behavior (self-medication) among Indonesian people, especially in West Sumatra Province, continues to increase. Without knowledge about the correct use of drugs, people will be at risk to drug use problems. Therefore, education on drug use needs to be implemented to increase public knowledge regarding drug use. By increasing their knowledge, the public will have rational drug use behavior. The aim of this community outreach is to increase public knowledge regarding the use of over-the-counter drugs and limited over-the-counter drugs in treating health problems. The method of activity carried out is education through face-to-face home visits. This activity was carried out in Nagari Sikucur, V Koto Kampung Dalam District, Padang Pariaman Regency. There were 30 community members or family representatives who were the targets of this drug use education and home visit. The implementation of this activity involved five teams consisting of pharmacy lecturers with pharmacists’ qualification, Master of Pharmacy students who had registered as pharmacists, and Bachelor of Pharmacy students. The activity started with an introduction, continued with a pre-test, providing education, post-test, and handing over self-medication drug packages to the community. The results of this home visit-based education show that the community's knowledge score regarding drugs is higher than before the education. It can be concluded that the objectives of this activity were achieved well. To achieve better activity results, preliminary studies, collaboration with stakeholders, time allocation, and adequate technical preparation of activities are required.